Estimates of age of individuals, locomotion speed and possible activity from human footprints at Monte Hermoso site 1 - Vassallo, Aldo Iván (2021)
The Monte Hermoso 1 archaeological site (Buenos Aires province, Argentina), shows an abundant record of human footprints, dated to ~ 7000 BP, which were imprinted on a mixohaline marsh shores. The objective of this study was to estimate the age and locomotion speed corresponding to 15 tracks of individuals, based on the original data of Bayón & Politis (1996). Age estimates were made based on growth curves from the literature. The estimated ages, corresponding to children and adolescents between 2.5 and 14.5 years, and possibly 1 juvenile-young adult, generally agree with previous interpretations. The locomotion speed was estimated from the empirical relationship between the dimensionless speed (Froude number) and the dimensionless stride length. Estimated speeds were in the range of 3-12km/h and could be classified into: 1) speeds compatible with those of hunting gathering in children of similar age (≤3km/h), 2) speeds compatible with comfort walking, in the range between 3.8 and 4.6 km / h, associated with a lower energy cost, perhaps for exploration of the surrounding territory, and 3) speeds>5km/h compatible with play, chasing a small prey, or simply an escape. The methodology used in this study to estimate locomotion speed revealed a diversity of locomotor patterns in the individuals who left their tracks at the Monte Hermoso 1 site, which could improve assessments about associated behaviors.